Mothers’ Use of Gestures and their Relationship to Children’s Lexical Production - Minto-García Aline; Alva Canto Elda A.; Arias-Trejo Natalia (Psychology of Language and Communication, 2020)
This study examines the relationship between mothers’ use of gestures and the lexical production of their children, measured in a joint book-reading task. Fifteen mother-child dyads participated, all monolingual native speakers of Mexican Spanish. Children were boys and girls with typical development, aged 48 months. Each reading session was videotaped and analyzed to calculate the gestural production of mothers and the lexical production of children. The results showed a significant positive correlation between the number of mothers’ gestures and the number of distinct words used by the children. Mothers’ gestural communication was related to the size of the vocabulary children produced in joint book-reading.